Enhancing semantic congruity effects with category-contingent comparative judgments - Leth-Steensen, Craig; Petrusic, William M.; Shaki, Samuel (Frontiers in Psychology, 2014)
In each of two experiments the direction of a binary comparison was contingent on the category of the stimulus pair. In one experiment, participants had to compare the size of animals from memory. On congruent trials, they had to select the smaller animal if both were small and the larger if both were large and on incongruent trials they selected the larger if both were small and the smaller if both were large. In a second experiment, participants had to compare visual extents and the direction of the comparison was contingent on whether the lines were short or long. RTs were increased and semantic congruity effects were greatly amplified with the category contingent instructions relative to the conventional non-contingent instructions, precisely as predicted by the class of evidence accrual models of decisional processing and contrary to the single sample stage models of the semantic congruity effect.